Strategies to Improve Entertainment Tax Compliance: Study Case at the Office of UPT Region VI Bapenda Medan City - Rezeki, Sri Gusti; Maidalena (International Humanity Advance, Business & Sciences, 2025)
This study discusses strategies for improving entertainment tax compliance at UPT Region VI Bapenda Medan City, which is an important part of the Regional Original Income (PAD). This study identifies the low level of entertainment tax compliance in Indonesia, which only reached 62% nationally and 55% in Medan City in 2022. Factors influencing non-compliance include weak supervision, low taxpayer awareness, and the complexity of tax mechanisms. Using a qualitative descriptive approach, this study explores the impact of non-compliance and proposes a compliance model-based strategy that includes four levels: (1) "willing to do the right thing", (2) "try to, but don't" t always succeed", (3) "don't want to comply", and (4) "have decided not to comply". The proposed strategy includes improving services, education, and strict law enforcement. The results of the study indicate that a comprehensive approach that combines persuasive, educational, and repressive elements can create a fairer and more transparent tax system, as well as encouraging taxpayers' awareness of the importance of their contribution to regional development.